2015
DOI: 10.1161/strokeaha.115.010088
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-Inducible C-Type Lectin/Spleen Tyrosine Kinase Signaling Pathway Contributes to Neuroinflammation After Subarachnoid Hemorrhage in Rats

Abstract: Background and Purpose Mincle (macrophage-inducible C-type lectin, CLEC4E) receptor is reported involved in neuroinflammation in cerebral ischemia and traumatic brain injury. This study was designed to investigate the role of Mincle and its downstream Syk signal pathway in early brain injury after SAH in a rat model. Methods Two hundreds and fifteen (215) male Sprague-Dawley rats (280–320g) were subjected to endovascular perforation model of SAH. SAH grade, neurological score, and brain water content were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 37 publications
5
69
0
Order By: Relevance
“…The findings are consistent with those of recently reported studies that have shown increased Mincle expression in the brains of humans and rodents after brain injury (14,15). These data, as well as the data presented here, allowed us to hypothesize that the Mincle may be an important sensor of nonphysiological cell death or cell stress that recognizes endogenous molecules released from damaged tissues and subsequently induces inflammation.…”
Section: Mincle Is a Prr In The Skin That Is Highly Inducible In Respsupporting
confidence: 93%
“…The findings are consistent with those of recently reported studies that have shown increased Mincle expression in the brains of humans and rodents after brain injury (14,15). These data, as well as the data presented here, allowed us to hypothesize that the Mincle may be an important sensor of nonphysiological cell death or cell stress that recognizes endogenous molecules released from damaged tissues and subsequently induces inflammation.…”
Section: Mincle Is a Prr In The Skin That Is Highly Inducible In Respsupporting
confidence: 93%
“…The data indicate that MK is a genetic factor that regulates the neuroinflammatory effects induced by this type of psychostimulants. In this context, it is also important to note that MK expression and signaling are activated in the brain after administration of different drugs of abuse [3335]. Taking together, our data suggest that the previously shown neuroprotective effects of MK against drug-induced neurotoxicity [20, 36] could be related to its ability to prevent neuroinflammation.…”
Section: Discussionsupporting
confidence: 54%
“…Specifically, Mincle expression was found to be upregulated during ischemic stroke, whereas inhibition of Mincle signaling via Syk blockade led to a significant decrease in the volume of cerebral infarct and brain swelling 34 . Similarly, Mincle signaling affects neuro-inflammation after subarachnoid hemorrhage and traumatic brain injury 35, 36 . Mincle deletion has also been shown to mitigate obesity-induced insulin resistance in mice fed high-fat diets 37 .…”
Section: Discussionmentioning
confidence: 99%